Tubulin folding: the special case of a beta-tubulin isotype from the Antarctic psychrophilic ciliate Euplotes focardii - Pucciarelli, Sandra; Chiappori, Federica; Sparvoli, Daniela; Milanesi, Luciano; Miceli, Cristina; Melki, Ronald (Polar Biology, 2013)
International audience Folding assistance is a fundamental requirement of certain proteins, and it may be subjected to physicochemical constraints in case of organisms adapted to polar temperatures. Limited information is available about protein folding in the polar environment. Folding of tubulin provides one of the few studied cases. Here, we report a pilot folding analysis of a divergent beta-tubulin isotype, named EFBT3, from the Antarctic psychrophilic ciliate Euplotes focardii. To attain its native monomeric structure, beta-tubulin needs the assistance of the eukaryotic class II chaperonin CCT and cofactor A (CofA). The in vitro folding reaction of EFBT3 with CCT and CofA purified from rabbit did not generate any folded product. In contrast, the reaction performed with the rabbit reticulocyte lysate, that contains all the chaperones required for efficient tubulin folding, was productive, suggesting that additional factors besides purified CCT and CofA are required for EFBT3 to attain its monomeric structure. We also demonstrated that the rare Cys281 of EFBT3 is critical for the folding reaction. Model predictions indicate that EFBT3 binds to CofA differently from yeast beta-tubulin, suggesting a diverse folding mechanism that may be correlated with microtubule cold adaptation.